2006
DOI: 10.1007/s10640-005-3605-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Risk Characteristics on the Willingness to Pay for Mortality Risk Reductions from Electric Power Generation

Abstract: The objective of this study is to estimate willingness to pay (WTP) for the reduction of mortality risks caused by fossil fuel (natural gas, coal and oil) versus nuclear electric power generation systems and to examine the influence of risk characteristics involved with electric power generation on WTP. A choice experiment was conducted to achieve these objectives. The attributes for nuclear risks in the experiment included the probability of disasters and the expected losses if a disaster occurs. We find evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 11 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…They confirmed a positive link between risk perception and disaster preparedness. According to Itaoka et al [40], as willingness to pay is sensitive to expected mortality, the higher the risk, the higher the willingness to pay. They demonstrated that the willingness to pay for reducing deaths from a nuclear disaster is about 60 times the willingness to pay for reducing fossil-fuel generation-related deaths.…”
Section: Perceived Riskmentioning
confidence: 99%
“…They confirmed a positive link between risk perception and disaster preparedness. According to Itaoka et al [40], as willingness to pay is sensitive to expected mortality, the higher the risk, the higher the willingness to pay. They demonstrated that the willingness to pay for reducing deaths from a nuclear disaster is about 60 times the willingness to pay for reducing fossil-fuel generation-related deaths.…”
Section: Perceived Riskmentioning
confidence: 99%
“…Advantages and disadvantages of labelling in CE are subject of an on-going discussion in environmental CE literature and beyond de Bekker-Grob et al, 2010;Doherty et al, 2011;Itaoka et al, 2006;Jacobsen et al, 2008). This study aims at determining the impact of labelling on WTP estimates related to natural hazard protection.…”
Section: Discussionmentioning
confidence: 99%
“…7 Finally, SP methods cater to a variety of contexts and causes of death, allowing researchers to test if, for example, accidental mortality risks are valued differently from causes of death usually linked with environmental exposures. SP methods have been used to elicit the willingness to pay for risk reductions in a variety of contexts, including transportation and road safety, (40,41) contaminated site cleanup, (42,43) and risks from power generation, (44) among others. In fact, in a recent meta-analysis, Lindhjem et al (20) identify 76 SP studies, which were conducted in 38 different countries, and cover mortality risks in environmental, health, and transportation contexts.…”
Section: Background and Literature Reviewmentioning
confidence: 99%